Differences between the 2018 and 2019 stratospheric polar vortex split events. (14th August 2020) - Butler, Amy H.; Lawrence, Zachary D.; Lee, Simon H.; Lillo, Samuel P.; Long, Craig S.
Abstract : Two recent occurrences in February 2018 and January 2019 of a dynamic split in the Northern Hemisphere stratospheric polar vortex are compared in terms of their evolution and predictability. The 2018 split vortex was associated with primarily wavenumber‐2 wave forcing that was not well predicted more than 7–10 days ahead of time, and was followed by persistent coupling to the surface with strong weather impacts. In 2019 the vortex was first displaced by slow wavenumber‐1 amplification into the stratosphere, which was predictable at longer lead times and then split; the surface impacts following the event were weaker. Here we examine the role of large‐scale climate influences, such as the phase of the El Niño–Southern Oscillation, the Quasi‐biennial Oscillation and the Madden–Julian Oscillation, on the wave forcing, surface impacts and predictability of these two events. Linkages between the forecast error in the stratospheric polar vortex winds with the forecast error in the Quasi‐biennial Oscillation and Madden–Julian Oscillation are examined. Abstract : The stratospheric polar vortex experienced a dynamic weakening and split into two vortices in both February 2018 and January 2019. The planetary wave forcing before the events, and the coupling from the stratosphere to the surface after the events, were quite different, which influenced their predictability. We investigate the role of large‐scale climate patterns in these differences.